Lord of the Wings - The Making of Free Form Architecture (2015)
Buildings are neither conceived nor realized by architects in a vacuum; the architect forms part of a larger team of builders, craftsmen, engineers and other experts who join forces to bring together their diverse fields of knowledge.This book describes the design and development of the building process for the wings at the Yitzhak Rabin Centre in Tel Aviv, and demonstrates how collaborative building, technical design and development can lead in an integrated and innovative, but risky process to an extreme innovation, an Octatube ‘Moonshot’. The challenge posed by the Rabin Centre wings was to develop an entirely novel technology for constructing free form shells. It is necessary for many disciplines to collaborate in such a process, and these must be coordinated throughout the entire process, including all of its unforeseen and experimental stages. The results of the process then have to be integrated into one technical artifact that satisfies all requirements and delivers effective answers or compromises in all of its life phases, be that conceptual design, material design, detail design, engineering, production, assembly, installation, loading behavior, functional use as a building, meaning of the building as an artifact (even as architecture) and, in both its local and global context, in its meaning as an integral part of the building.